Merging the Interfaces of Different Shape‐Shifting Polymers Using Hybrid Exchange Reactions. Issue 1 (18th November 2022) - Liang, Huan; Zhang, Shuai; Liu, Yawen; Yang, Yang; Zhang, Yubai; Wu, Yahe; Xu, Hongtu; Wei, Yen; Ji, Yan
Abstract: Sophisticated shape‐shifting structures and integration of advanced functions often call for different‐chemistry‐based polymers (such as epoxy and polyurethane) in a unified system. However, permanent cross‐links pose crucial obstacles to be seamless. Here, merging interfaces via hybrid exchange reactions among different dynamic covalent bonds (including ester, urethane, thiourethane, boronic–ester, and oxime–ester linkages) is proposed, breaking the long‐lasting restriction that these widely used bonds only undergo self‐exchange reactions. Model compound studies are conducted to verify that hybrid exchange reactions occur. As demonstrations, different liquid crystal elastomers are tenaciously joined into coherent assemblies, with the desired biomimetic structures (e.g., flying fish containing stiff and flexible parts) and rare deformation modes (e.g., flower blooming upon both heating and cooling). Besides connecting polymers, hybrid exchange reactions also facilitate the creation of new materials through cross‐fusion of different polymers. In addition to the polymers used in this work, hybrid exchange reactions can be adapted to other polymers based on similar mechanisms and beyond. Besides shape‐shifting‐related areas (e.g., soft robots, flexible electronics, and biomedical devices), it may also foster innovation in other fields involving general polymers, as well as promote deeper understanding of dynamic covalent chemistry. Abstract : Hybrid exchange reactions (among ester, urethane, thiourethane, boronic–ester, and oxime–ester linkages) enable stable seamless bonding of covalently cross‐linked networks made by different chemistry, as well as to produce new materials by cross‐fusion. Distinctive multimaterial 3D shape‐shifting structures are demonstrated since this strategy facilitates flexible design in morphology and integration of diverse properties in a monolithic recyclable and potentially healable system.